The Prevalence of Risk Factors of Breast Cancer in Different Age Groups of the Female Population of the Omsk Region - N. G. Shirlina; V. L. Stasenko; V. A. Shirinskiy; T. M. Obukhova (Эпидемиология и вакцинопрофилактика, 2017)
The paper estimates the prevalence of the main risk factors for breast cancer (BC) in different age groups of the female population of the Omsk Region. Priority groups for the correction of risk factors in five age intervals were identified. According to the results of an integrated assessment of the aggregate of risk factors at different ages of women, the age group 60-69 years old was in the first ranking place for the priority of preventive measures, the second group was 70 years or more, the third group included a group of 30-39 year old women. The specific weight of the corrected risk factors in this group of respondents was 85.7%, which determines the potential of preventive measures.